Developing An Interactive English Teaching Module for Visual Communication Design Students using Google Sites at Grade X SMK Negeri 1 Mataram (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This research addresses a critical gap in independent curricula (IKM) that fails to meet Visual Communication Design (VCD) students' specific needs for professional English communication. This study addresses the lack of industry-specific English learning materials for Visual Communication Design (VCD) students by developing an interactive teaching module using Google Sites. Guided by the ADDIE model within an R&D framework, the research employed a mixed-methods approach to collect both qualitative and quantitative data. Qualitative data from teacher interviews and document analysis were processed through Miles and Huberman's model. Quantitative data included expert validation using a four-point Likert scale and responses from 32 student participants. The developed module featured a whole-part-whole framework with visual branding content reflecting industry practices. Implementation through Google Sites with interactive features achieved a 90% expert validation score, indicating high feasibility. Student feedback data revealed strong positive responses across multiple dimensions: 89% satisfaction with practical examples, 85.9% for content comprehensibility, and particularly enthusiastic reception of the industry-relevant materials. During evaluation, student input led to specific improvements in text display. The research successfully bridges the gap between general English teaching and vocational preparation by creating an empirically validated, interactive learning tool that equips VCD students with the specialized English communication skills essential for success in the visual design industry.